2016
DOI: 10.3390/nu8020071
|View full text |Cite
|
Sign up to set email alerts
|

Association of Body Composition with Curve Severity in Children and Adolescents with Idiopathic Scoliosis (IS)

Abstract: The link between scoliotic deformity and body composition assessed with bioimpedance (BIA) has not been well researched. The objective of this study was to correlate the extent of scoliotic-curve severity with the anthropometrical status of patients with idiopathic scoliosis (IS) based on standard anthropometric measurements and BIA. The study encompassed 279 IS patients (224 girls/55 boys), aged 14.21 ± 2.75 years. Scoliotic curve severity assessed by Cobb’s angle was categorized as moderate (10°–39°) or seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 38 publications
(62 reference statements)
1
23
3
Order By: Relevance
“…Good correlation was found between BIA and dual-energy X-ray absorptiometry in the study of de Lorenzo et al [ 33 ], Loveday et al [ 34 ], and Kehoe et al [ 35 ]. Moreover, our recent study confirmed its utility in children and adolescents with idiopathic scoliosis [ 36 ].…”
Section: Discussionmentioning
confidence: 55%
“…Good correlation was found between BIA and dual-energy X-ray absorptiometry in the study of de Lorenzo et al [ 33 ], Loveday et al [ 34 ], and Kehoe et al [ 35 ]. Moreover, our recent study confirmed its utility in children and adolescents with idiopathic scoliosis [ 36 ].…”
Section: Discussionmentioning
confidence: 55%
“…Two studies only used the WHO definition (BMI Z score) [45,46], and no study has compared the prevalence of AIS based on the three standardized definitions of low BMI. In a previous study, when the WHO BMI (kg/m 2 ) percentile charts were used, a significant difference was found between the severe AIS group (Cobb's angle >40 ) and moderate AIS group (Cobb's angle 10 ~3 9 ), but the use of the BMI Z score (SD) of the WHO did not present any differences between the two groups [47]. This finding is speculated to be due to the underestimation of AIS prevalence by the use of BMI Z score of the WHO cutoff.…”
Section: Discussionmentioning
confidence: 92%
“…According to standard procedures [29], height was measured using a wall-mounted stadiometer to the nearest 0.1 cm. Body weight was measured with a digital scale to the nearest 0.1 kg.…”
Section: Methodsmentioning
confidence: 99%